Iowa RBA, September 22, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for September 22, 1997. Highlights of the update include a report of 131 species seen on field trips to the Iowa City-Cedar Rapids area held during the IOU fall meeting, including American Bittern and Nelson's Sharp-tailed Sparrows. Also of note were sightings of Lark Buntings, a Red-necked Phalarope, and an Evening Grosbeak. Also included are handwritten notes for the next week's update with an update on the continued presence of Eurasian Collared Doves in Grinnell. Epson - sheet feed/flatbed